NOD2 mRNA Expression and NFkappaB Activation in Dogs with Lymphocytic Plasmacytic Colitis. (18th April 2013) - Okanishi, H.; Hayashi, K.; Sakamoto, Y.; Sano, T.; Maruyama, H.; Kagawa, Y.; Watari, T.
<x xml:space="preserve">Abstract</x> Background Nucleotide Oligomerization Domain Two (NOD2) is suggested to be an intracellular pathogen‐associated molecular pattern recognition molecule. NOD2, plays a key role against bacteria by triggering a host defense response through activation of the transcription factor NFkappaB and subsequent proinflammatory cytokine production. NOD2 recently was reported to be overproduced in inflamed colonic mucosa in Crohn's disease, and to be accompanied by a significant increase in NFkappaB activity. However, few studies to date have investigated intercellular signaling molecules in dogs with lymphocytic plasmacytic colitis (LPC). Hypothesis NOD2 mRNA expression and NFkappaB activation are increased in mucosal biopsies of LPC dogs as compared with control dogs. Animals Five healthy dogs and 19 dogs with LPC. Methods Descending colon biopsies were obtained endoscopically. Expression of NOD2 mRNA was evaluated by semiquantitative RT‐PCR in the colonic mucosa. NFkappaB binding activity was assessed by electrophoretic mobility shift assay. Results NOD2 mRNA expression was approximately 63% greater in LPC dogs than in healthy controls (P = .019). NFkappaB binding activity was approximately 45% higher in the inflamed colonic mucosa of the LPC dogs, as compared with healthy controls (P = .011). No correlations were observed among NOD2 mRNA expression levels, NFkappaB binding activity, and CIBDAI in LPC dogs. Conclusions and Clinical Importance NOD2 mRNA and NFkappaB activity were significantly higher in the inflamed colon of dogs with LPC, as compared with healthy controls. Our data suggest that NOD2 and NFkappaB play an important role in the pathogenesis of LPC.